Elliptical Ring Antenna Excited by Circular Disc Monopole for UWB Communications - Krittaya Nakprasit; Arnon Sakonkanapong; Chuwong Phongcharoenpanich (International Journal of Antennas and Propagation)
This research proposes a compact elliptical ring antenna excited by a circular disc monopole (CDM) for ultra-wideband (UWB) communications. In the study, time- and frequency-domain pulse distortions of the antenna in the transmission mode were characterized by magnitude and phase of the antenna transfer function (Hrad). The results showed that the gain and magnitude of Hrad in the boresight direction are sufficiently flat with linear phase response. The average antenna gain is 3.9 dBi over the UWB spectrum. The antenna also exhibits low pulse distortion with the correlation factors (ρ) of 0.98 and 0.93 for the fifth-order derivative Gaussian pulse and modulated Gaussian pulse with 6 GHz band rejection. The CDM-excited elliptical ring antenna possesses several attractive features, including wide bandwidth, flat gain, compactness, low cost, and low distortion.